Analysts’ Advice on IPOs and Regulations: An Analysis of United States and European Markets - Boissin, Romain; Madureira, Leonardo; Singh, Ajai K. (Journal of Accounting and Finance, 2023)
Using recommendations and target prices on initial public offerings (IPOs), we examine the impact of regulations in the United States (US) and European Union (EU) markets that were aimed at curbing conflicts of interest in sell-side research. Conflicted analysts, proxied by whether their brokerage houses (henceforth brokers) acted as lead or co-managers in the IPO process, issued more optimistic recommendations in the US and EU markets in the pre-regulatory period. However, this extra optimism is absent after the adoption of regulations. A similar pattern emerges when examining the returns implied from US IPO target prices. Investors seem to capture the pattern, as they discount optimistic recommendations from conflicted analysts before, but not after, the new regulations. Using the staggered implementation of the new regulations—whereby US regulations take place strictly before any changes in the EU markets—we show that US brokers take the new modus operandi to Europe. In the time between the passage of US and EU regulations, US brokers in the lead role acted similarly in Europe to how they acted in the US. The EU brokers continued with their optimistic projections until the implementation of the local regulations.